1957
DOI: 10.1104/pp.32.4.346
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Salts on Pyruvate Kinase from Tissues of Higher Plants

Abstract: The enzyme pyruvate kinase which catalyzes the reversible transfer of phosphate from phosphoenolpvruvate (PEPA) to adenosine diphosphate (ADP) yielding pyruvate and adenosine triphosphate (ATP) is widely distributed in living organisms (2, 3, 4, 8, 9, 11, 15). Lohmann and AMeverhof (11) in 1934 demonstrated that the activity of pyrtuvate kinase from rat muscle was dependent on the presence of Mg++ in the assay medium. Utter and Werkman (22) reported that extracts from Escherichia coli contained pyruvate kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1
1

Year Published

1963
1963
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 5 publications
1
36
1
1
Order By: Relevance
“…At maximum enzyme activity the substitution of the PO43-salt gave 120 % of the activity obtained with Cl-whereas in the presence of the NO;-anid SO (2). These results are in contrast to the observation of Na' being an activator for pyruvate kinase isolatecd from higher plants (8).…”
contrasting
confidence: 55%
“…At maximum enzyme activity the substitution of the PO43-salt gave 120 % of the activity obtained with Cl-whereas in the presence of the NO;-anid SO (2). These results are in contrast to the observation of Na' being an activator for pyruvate kinase isolatecd from higher plants (8).…”
contrasting
confidence: 55%
“…Previous investigation (9) has shown that neither Tris nor chloride ions appreciably influence the activity of pyruvate kinase. Experiments conducted to compare the inhibitory effect of Na+ or K+ molybdate with that of Tris molybdate showed no consistent differences.…”
mentioning
confidence: 99%
“…Sodium ions activated the enzyme slightly and Li+ and Ca+ + were inhibitory. Miller and Evans (9) demonstrated that pyruvate kinase from a series of higher plants also require K+, NH + or Rb+ and that a concentration near 0.04 N was necessary for maximum reaction velocity.…”
mentioning
confidence: 99%
“…The extraction and assay of pyruvate kinase were conducted by using the slightly modified method described by Miller and Evans (12). For preparation of the extract, 2 g of leaves were homogenized in 10 ml of 50 mm tris buffer, pH 7.4, and the mixture was centrifuged at 25,000g for 10 min.…”
Section: Methodsmentioning
confidence: 99%